Design of a solar energy system for use in home in Singapore - Tang, Shukong. (2013)
Solar power, as a form of renewable energy, has been playing an important role in providing us an alternative way to generate power that is eagerly demanded all over the world. Economy growth, for the modern world today, is tremendously dependent on energy, while there is also a call for clean and sustainable resources. Therefore, solar energy becomes a vital investment as well as an important research filed in a lot of countries.